4x+7(-3x-13)=11

Simple and best practice solution for 4x+7(-3x-13)=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+7(-3x-13)=11 equation:


Simplifying
4x + 7(-3x + -13) = 11

Reorder the terms:
4x + 7(-13 + -3x) = 11
4x + (-13 * 7 + -3x * 7) = 11
4x + (-91 + -21x) = 11

Reorder the terms:
-91 + 4x + -21x = 11

Combine like terms: 4x + -21x = -17x
-91 + -17x = 11

Solving
-91 + -17x = 11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '91' to each side of the equation.
-91 + 91 + -17x = 11 + 91

Combine like terms: -91 + 91 = 0
0 + -17x = 11 + 91
-17x = 11 + 91

Combine like terms: 11 + 91 = 102
-17x = 102

Divide each side by '-17'.
x = -6

Simplifying
x = -6

See similar equations:

| 6(-4+4y)-18=4-4y | | 8x+x+x=70 | | 6(-4+4y)-18=4y | | 9x-y=48 | | (5xy^4)^3/7 | | (21/18)^2 | | 21/18^2 | | C=2(pi)30 | | 5m+3x+8m= | | 8x+7x-6x-5=58 | | x^2+4x-0.24=0 | | x^2+4x+0.24=0 | | 26+p=31 | | dy/dx=0 | | 126=(h+4)(h+3)(h) | | (u^1/4)/(u^10/4) | | 10(s-6)=-132 | | 5x/2122=12668 | | y=-x+32.7 | | 1/14=1/11=1/x | | 5k+7=2k+17 | | 5y=12-4 | | C=2(pi)0.5 | | C=2(pi)2.1 | | 6s-9+47= | | x=-y+20 | | x/14=72/7x | | x=32.7-y | | (2-x)(3+x)=0 | | 4/7y=1/8 | | 11x+x+x=78 | | C=2(pi)(2/3) |

Equations solver categories